A Struggle for Framing and Interpretation: The Impact of the 'Basic Income Experiments' on Social Policy Reform in the Netherlands. Issue 3 (September 2022) - Roosma, Femke
In the period from 1st October 2017 to 31st December 2019, the Dutch government allowed several municipalities to carry out so-called 'basic income experiments', 'trust' experiments, or 'experiments low in regulation'. These experiments focused on giving exemptions on obligations attached to social benefits, allowing people to keep extra earnings on top of their social assistance benefits, and providing more guidance in finding work. In this paper, I critically evaluate the extent to which these experiments have had an effect on social policy in the Netherlands in both the short and long run. For municipalities, the main goal of these experiments was to examine whether an approach focused on trust and intrinsic motivation would lead to increased labour market participation and higher wellbeing. The national government approved the experiments; but in its evaluation, it focused solely on the outflow to work in line with the existing workfare approach. In the short run, the effects of the experiments appeared disappointing for those with the ambition of fundamentally reforming the social security system. However, in the struggle for framing and interpretation, advocates of a different social policy approach obtained success in the long run. Although the Participation Act was not initially amended, the recent coalition agreement of the new Government does propose a change related to the outcomes of the experiment; and in recent party manifestos, there are more far-reaching proposals to change social policy in the direction of a universal basic income.